Predictive factors for the duration until return to work after surgery for work‐related rotator cuff syndrome: A prospective study of 92 workers. Issue 12 (19th September 2021) - Pichené‐Houard, Anne; Paysant, Jean; Claudon, Laurent; Paris, Nicolas; Michel, Blaise; Jacquot, Adrien; Martinet, Noël; Sirveaux, François; Wild, Pascal
Abstract: Background: Return to work (RTW) after surgery for a work‐related rotator cuff disorder (WRRCD) is often difficult. The study's purpose was to identify preoperative factors predicting RTW. Methods: Ninety‐two workers with a WRRCD were identified by four surgeons. Before surgery, the workers completed a series of standardized questionnaires related to working conditions, health, and health beliefs. They were followed up prospectively for 20 months. Statistical analysis was based on single and multiple‐factor Cox models of the duration of absence from the time of surgery until RTW. Results: The median age at inclusion was 49 years (27–62), with 52 women included (57%). Sixty‐one subjects (66%) were employed in highly physically demanding jobs. Forty‐two (46%) stayed at work until their surgery, whereas preoperative sick leave exceeded 100 days in 20 subjects (21%). Twenty months after surgery, 14 were still not back at work. For the other participants, the mean duration until RTW was 225 days (SD 156). In the fully adjusted model, variables that were significantly predictive of the duration until RTW were: work physical demand levels, preoperative sick leave, the number of body parts causing pain or discomfort in the last 12 months, self‐assessed 2‐year workability, and the Readiness for RTW (RRTW) Scale. Conclusions: Several physical, psychological, and work‐related factors, easily recorded, can be identified preoperatively. They may be predictive of delayed return, loss of employment, or employability as a result of shoulder surgery.